Career-decision making of university students: cross-cultural comparisons between Mongolia and Japan - Damdin, Dulguun; Yamashita, Toshiyuki; Ishihara, Masami (Proceedings of the Mongolian Academy of Sciences, 2021)
The purpose of this study was to examine and compare Mongolians (118 men and 252 women) and Japanese (158 men and 201 women) university students’ awareness related to their occupation and their motivations for entering university. The survey focused on the vocational motives, university performance/experiences, and motivations for entering university. The analyses showed that although Mongolian and Japanese students have similar occupational views, there are some cultural differences that can be mainly identified with the recent historic developments and social changes both the nations experienced (e.g socialistic era in Mongolia).